Mureidomycin A, a new inhibitor of bacterial peptidoglycan synthesis. - Isono, F (1991)
Mureidomycin A (MRD), a novel peptidylnucleoside antibiotic with antipseudomonal activity, inhibited not only peptidoglycan synthesis but also lipid-intermediate formation from UDP-N-acetylmuramyl (MurNAc)-pentapeptide and UDP-N-acetylglucosamine in an in vitro peptidoglycan-synthesizing system, using ether-treated cells of Pseudomonas aeruginosa. Both types of inhibition by MRD disappeared when UDP-MurNAc-pentapeptide was preincubated with ether-treated cells. Moreover, MRD completely inhibited lipid-intermediate I (undecaprenyl-p-p-MurNAc-pentapeptide) formation at a concentration below the MIC. From these results, it was concluded that the real target of MRD's action was translocase, which catalyzes lipid-intermediate I formation from UDP-MurNAc-pentapeptide and a lipid carrier.